First Record of Pseudomyrmex acanthobius Emery in Brazilian Pantanal - Aranda, Rodrigo; Olivier, Renan; Ferraro, Alexandre (EntomoBrasilis, 2016)
Abstract. Associations between ants and plants may be described, in some cases, as mutualisms. Ants use plant structures as sites for nesting and in return they offer protection against herbivory. This paper reports for the first time the association between Pseudomyrmex acanthobius Emery nest in subterranean structures of Aspilia grazielae J.U.Santos, an endangered endemic plant species, in Corumbá, Pantanal domain. Additionally, this record reveals a new aspect of the ecological niche and extends the geographic distribution of P. acanthobius. Primeiro Registro de Pseudomyrmex acanthobius Emery no Pantanal Brasileiro Resumo. A associação entre formigas e plantas pode ser descrita em alguns casos como mutualismo. Estruturas de plantas, como locais de nidificação, atraem algumas espécies de formigas em troca da proteção anti-herbivoria. Este trabalho registra pela primeira vez a nidificação de Pseudomyrmex acanthobius Emery em estrutura subterrânea de Aspilia grazielae J.U.Santos, espécie endêmica e ameaçada de extinção na região de Corumbá, no domínio Pantanal. Adicionalmente, esse registro revela nova amplitude do nicho ecológico e amplia a distribuição geográfica prevista de P. acanthobius.